2012
DOI: 10.2478/v10230-012-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Scientific and Technological Progress, Political Beliefs and Environmental Sustainability

Abstract: With the development of science and technology, a basically optimistic ideology of progress has emerged. This deterministic attitude has been challenged in recent decades as a result of harmful side-effects generated by the way technology and science have been approached and used. The study presented here is a part of a larger international and comparative study dealing with global/environmental issues related to political orientation, science and technology. 3 080 pre-service teachers from Finland, Greece, Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The subak is a complex adaptive system that has been sustained for more than two millennia through co-evolution between the Balinese farmers and their local environment rich with socio-scientific values, concepts, and issues. Hence, the system is an excellent model to study higher concerns about the relationship between scientific and technological issues in the development of a sustainable society [20].…”
Section: Resultsmentioning
confidence: 99%
“…The subak is a complex adaptive system that has been sustained for more than two millennia through co-evolution between the Balinese farmers and their local environment rich with socio-scientific values, concepts, and issues. Hence, the system is an excellent model to study higher concerns about the relationship between scientific and technological issues in the development of a sustainable society [20].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, advances in sciences and technology are seen predominantly from a pessimistic rather than an optimistic perspective. An international study (Makrakis, 2012a) found a strong and pessimistic connection between environmental consciousness and attitudes towards the role and impact of science and technology on society.…”
Section: The Sustainability Crisis and The Issue Of Justicementioning
confidence: 99%
“…Technology has not alleviated the daily struggle of millions of people and children who face hunger and malnutrition, who have been displaced by the floods due to climate change and profit-driven deforestation, who have no access to education, water and other basic human needs. An international and comparative study among student-teachers from Finland, Greece, Sweden, Japan and Holland (Makrakis, 2012b) shows that none of the sample country respondents identified themselves as optimists concerning the role and impact of science and technology on the society and the environment. The no-stance and the pessimistic attitudes towards technology and science seem to derive from the human and environmental costs associated with science and technology development.…”
Section: Total (%)mentioning
confidence: 99%